Ecological restoration efforts in tropical rural landscapes: Challenges and policy implications in a highly degraded region. (June 2018) - Toledo, Renato Miazaki; Santos, Rozely Ferreira; Verheyen, Kris; Perring, Michael P.
Highlights: Rural landscapes offer challenging conditions for Tropical Forest Restoration (TFR). Drivers of TFR success has been widely altered by agricultural land uses. Lands offered for restoration are often associated with poor conditions for TFR. Opportunities for cost-effective TFR actions can be spatially assessed at fine scale. Strong commitment and long-term policies will likelly enable gradual progress in TFR. Abstract: Ecological restoration has received increasing attention as international agreements have set ambitious goals to mitigate environmental change and reshape degraded landscapes. However, current restoration activities sometimes remain modest in their success. In particular, tropical forest restoration has had mixed outcomes with variable cost-efficiency. Here, we address the need for taking into account the spatial context of restoration to inform policy initiatives that aim to improve the ecological and economic effectiveness of restoration. We accessed the spatial distribution of relevant characteristics for ecological restoration in an emblematic heavily degraded tropical region: São Paulo state, Brazil. We compared statewide patterns in soil erosion risk, distance to remnant habitat, and agricultural land use, to their characteristics in land voluntarily offered for active restoration. Based on this comparison, active restoration is likely to take place through small, low-priced parcels of land, usually in the context of substantial soil erosion risk and exacerbated deforestation. Restoration ecology predicts the need for expensive actions to assist a limited recovery process in such highly degraded conditions. This general pattern also suggests the necessity for long-term commitment among a broad set of social actors, combined to mitigation of degradation in adjacent remnants and agricultural lands. Active restoration may be complemented by spontaneous regeneration in areas with less adverse conditions. Policy makers therefore need to consider the complementarity of lands voluntarily offered for restoration, and land made available for restoration through other mechanisms. Our findings, likely applicable to other densely populated tropical regions, suggest that land-use policies need to address drivers of restoration success at a fine-scale to enable effective strategies. We suggest this can be achieved by spatial analyses that incorporate biophysical features that determine restoration opportunities and the likelihood of success.